The “Kingston Mills Murder” and the Construction of “Honour Killings” in Canadian News Media - Mason, Corinne L. (Atlantis, 2015)
In this article, I examine print media coverage of the 2009 “Kingston Mills Murder” case and how this enactment of patriarchal violence was interpreted though a cultural lens as “honour killings.” I also focus on how feminist and gender “experts,” in statements to the news media, interpreted the murders as the consequence of a “clash of civilizations.” Drawing on the work of Chandra T. Mohanty (2003), I argue that it essential that Western feminisms decolonize discursive constructions of the “Other” in order to create and sustain “communities of resistance” to patriarchal violence. By investigating this case, I also seek to provide a road map for imagining an alternative feminist response to “honour killings” based on Sherene Razack’s (1998) interlocking analysis.